2020
DOI: 10.1085/jgp.201912462
|View full text |Cite
|
Sign up to set email alerts
|

The mechanisms shaping CA2 pyramidal neuron action potential bursting induced by muscarinic acetylcholine receptor activation

Abstract: Recent studies have revealed that hippocampal area CA2 plays an important role in hippocampal network function. Disruption of this region has been implicated in neuropsychiatric disorders. It is well appreciated that cholinergic input to the hippocampus plays an important role in learning and memory. While the effect of elevated cholinergic tone has been well studied in areas CA1 and CA3, it remains unclear how changes in cholinergic tone impact synaptic transmission and the intrinsic properties of neurons in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 74 publications
2
18
1
Order By: Relevance
“…Because theta rhythm is a brain state characterized by elevated levels of acetylcholine, we approximately mimicked these conditions in the hippocampal slice preparation by bath application of 10 µM of the cholinergic agonist carbachol (CCh). Under these conditions, CA2 PNs depolarize and spontaneously fire rhythmic bursts of APs, and the properties of these AP bursts are tightly controlled by excitatory and inhibitory synaptic transmission ( Robert et al, 2020 ). Thus, we decided to examine how SuM input stimulation influenced CA2 PN firing under these conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because theta rhythm is a brain state characterized by elevated levels of acetylcholine, we approximately mimicked these conditions in the hippocampal slice preparation by bath application of 10 µM of the cholinergic agonist carbachol (CCh). Under these conditions, CA2 PNs depolarize and spontaneously fire rhythmic bursts of APs, and the properties of these AP bursts are tightly controlled by excitatory and inhibitory synaptic transmission ( Robert et al, 2020 ). Thus, we decided to examine how SuM input stimulation influenced CA2 PN firing under these conditions.…”
Section: Resultsmentioning
confidence: 99%
“…In the presence of CCh, CA2 PNs undergo a depolarization of the membrane potential that is followed by a period of AP firing as the membrane potential remains depolarized for several seconds, and then slowly hyperpolarizes until the next bursting event ( Robert et al, 2020 ). We observed that photostimulation of SuM inputs resulted in a striking reduction in the amount of time the membrane potential remained depolarized, and this is likely why the burst duration was significantly shorter in bursts with SuM photo-stimulation ( Figure 7F–G ; burst duration was 4.0 ± 1.1 s in control and 1.6 ± 0.5 s with photostimulation, n = 7; paired-T test, p=0.037).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, mice with genetically inactivated CA2 pyramidal neurons, also showed an inability to differentiate between novel and familiar conspecifics (Hitti & Siegelbaum, 2014). Noteworthy, cholinergic signalling has been shown to impact synaptic transmission and the intrinsic properties of CA2 neurons (Robert et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While area CA2 has been shown to play a significant role in several hippocampal processes including social memory formation (Hitti and Siegelbaum, 2014;Stevenson and Caldwell, 2014) sharp-wave ripple generation (Oliva et al, 2016) and spatial encoding (Kay et al, 2016), information about the local circuitry and cellular processes allowing these functions is lacking. There is mounting evidence that generalizations cannot be made from the rich understanding of areas CA1 and CA3, as neurons in area CA2 have been shown to have unique molecular expression profiles (Cembrowski et al, 2016;Lein et al, 2004), morphology (Bartesaghi and Ravasi, 1999;No, 1934) and cellular properties (Robert et al, 2020;Srinivas et al, 2017;Sun et al, 2014). Notably, and in contrast to area CA1, CA2 pyramidal neurons do not undergo NMDA-mediated synaptic plasticity (Dasgupta et al, 2020;Zhao et al, 2007).…”
Section: Introductionmentioning
confidence: 99%